Pemanfaatan Tumbuhan Penghasil Pestisida Ramah Lingkungan Terhadap Mortalitas Hama Keong Mas (Pomacea canaliculata Lamarck) Pada Tanaman Padi Sawah - Muhammad Riadh Uluputty (JURNAL PERTANIAN KEPULAUAN, 2023)
One of the main pests and many damaging rice plants is gold snails. The damage caused can reach 13.2–96.5%. This pest is difficult to control despite the application of pesticides. The purpose of the study was to determine the effect of organic pesticide-producing plants on the mortality of gold snail pests in rice fields. The experiment using Complete Randomized Design consisted of 5 treatments, namely: P0 (control), P1 (tubal root extract), P2 (soursop leaf extract), P3 (lemongrass extract), P4 (papaya leaf extract) and P5 (jatropha leaf extract). The results showed that the highest average consumption rate was found at P1 (70.73%) and the lowest at P0 (1.73%). The highest average mortality rate from this pest was found at P1 (80) and lowest at P0 (0) during the observation period 4 hours after application. While at 8-hour observations the average mortality was highest at P4 and P5 (60) and lowest at P0 (13) after application. The highest average death time velocity was observed at P1 (3) and lowest at P0 (0) in the observation period 4 hours after application, while the highest average death time speed 8 hours after application was found at P4 and P5 (5) and lowest at P0 (2).